Profiling float‐based observations of net respiration beneath the mixed layer. Issue 6 (29th June 2016) - Hennon, Tyler D.; Riser, Stephen C.; Mecking, Sabine
Abstract: We employ profiling floats with dissolved oxygen sensors to observe in situ temporal oxygen evolution below the mixed layer, allowing us to characterize net respiration of organic carbon in eight distinct regions over the globe. Export and export efficiency are generally high in locations with strong seasonal variability and low in locations of weak seasonality. Vertically integrated respiration is weakly, yet significantly, correlated with remote observations of chlorophyll, net primary production, and planktonic community size structure. These correlations suggest that regimes of high net primary production and large phytoplankton fuel elevated respiration at depth. Several regions of float‐based observations intersect with sites of other detailed observations (e.g., Hawaii and Sargasso Sea), which allows us to compare our results to independent studies. We find that there is good agreement among export production estimates at highly seasonal locations, and that float‐based observations may be biased low at weakly seasonal locations. We posit that the reason for the low‐latitude discrepancy is the relative steady state of oxygen concentration caused by weak seasonality and shallow wintertime mixed layer depths. Key Points: Profiling floats are used to estimate respiration, export production, and export efficiency in eight geographically distinct regions Generally, there is greater respiration and export at high latitude, although float estimates may be biased at low latitude Depth‐integrated respiration is significantly correlated to surface chlorophyll, net primary production, and planktonic size